THE ANALYSIS OF TENSES USED IN A CHILDREN BOOK; THE-NOT-SO-PERFECT PRINCESS-AND-NOT-SO-DREADFUL-DRAGON WRITTEN BY JAYNEEN SANDERS - Erna Pranata Putri (Asosiasi Dosen Muda Indonesia, 2023)
A grammatical term in English used to show an action has happened, is happening, or about to happen is called tenses. The main tenses in English are past tense, present tense, and future tense. Tenses are used in writings and non-writings. This research was conducted to find out the tenses used in the children book entitled The-Not-So-Perfect Princess-and-Not-So-Dreadful-Dragon written by Jayneen Sanders. This was analyzed using Betty Schrampfer Azar’s Theory. The method used in this research was qualitative method. The result showed that there were 66 data that consist of 38 data for past tense, 25 data for present tense, and 3 data for future tense. Past tense was used in narrative meanwhile present tense and future tense were used in directive sentences. The sentences in past tense described the characters and the events. The present tense described what the characters are feeing and stated a fact. Lastly, the future tense described the worries the characters feel.